1997
DOI: 10.1182/blood.v90.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Autologous Filgrastim-Primed Bone Marrow Transplantation Versus Filgrastim-Mobilized Peripheral Blood Stem Cell Transplantation in Lymphoma Patients

Abstract: Although a large amount of data is available on the effects of filgrastim (granulocyte colony-stimulating factor [G-CSF]) on the mobilization of stem cells in the circulation, data concerning its effects on bone marrow (BM) harvesting is scarce and controversial. We have designed a randomized trial comparing filgrastim-mobilized peripheral blood stem cell (PBSC) transplantation with filgrastim-primed autologous bone marrow transplantation (ABMT). Fifty-five patients affected by non-Hodgkin's (n = 38) or Hodgki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…However, the diagnoses of these patients were not mentioned in the paper and the time to PBSC engraftment was delayed compared to our data (11). In a recent randomized study in lymphoma patients, G-CSF primed BM was found to produce equally fast engraftment as G-CSF primed PBSC (12). This is in contrast to the findings in our study and may be due to different patient characteristics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the diagnoses of these patients were not mentioned in the paper and the time to PBSC engraftment was delayed compared to our data (11). In a recent randomized study in lymphoma patients, G-CSF primed BM was found to produce equally fast engraftment as G-CSF primed PBSC (12). This is in contrast to the findings in our study and may be due to different patient characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…The engraftment data from 15 double BM transplants and 7 double PBSC transplants in testicular cancer patients are shown in Table 2. There was no (8)(9)(10)(11)(12)(13)(14)(15)(16) difference in time to neutrophil or platelet engraftment between first and second transplantation in neither BM nor PBSC transplantations.…”
Section: Testicular Cancer Patientsmentioning
confidence: 99%
“…The advantage in the granulocyte and platelet recovery in the PSCT arm was also reflected in a significant reduction in number of days with fever and intravenous antibiotics, and less transfusions, further underscoring the advantage of applying PSCT over ABMT. A recent study suggested that the results of ABMT could be improved by using G-CSF-exposed bone marrow cells for 3 d (Damiani et al, 1997). In this setting, the difference in engraftment between PSCT versus ABMT almost disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a great variability in neutrophil recovery in the setting of ABMT, which will be related to previous chemotherapy regimens and the number of (stem) cells collected. Damiani et al (1997) reported a median of 13 d for neutrophil engraftment in ABMT patients. In contrast, a recent study with recombinant interleukin 3 (IL-3) given in the setting of ABMT demonstrated a neutrophil ($ 0´5 Â 10 9 /l) and platelet ($ 20 Â 10 9 /l) engraftment in the placebo arm after a median of 25 and 28 d respectively (Brouwer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human G-CSF is mainly applied to reduce febrile neutropenia in patients with non-myeloid malignancies that receive myelosuppressor drugs [2,3]. It is also recommended for treating congenital, cyclic or idiopathic neutropenia [4], to accelerate neutrophils recovery in bone marrow transplantation [5], to minimize other neutropenia [6][7][8][9] and for the mobilization of hematopoietic progenitor cells into the peripheral blood for collection by leukapheresis [10].…”
Section: Introductionmentioning
confidence: 99%